1993
DOI: 10.1901/jeab.1993.60-361
|View full text |Cite
|
Sign up to set email alerts
|

DRL Interresponse‐time Distributions: Quantification by Peak Deviation Analysis

Abstract: Peak deviation analysis is a quantitative technique for characterizing interresponse-time distributions that result from training on differential-reinforcement-of-low-rate schedules of reinforcement. It compares each rat's obtained interresponse-time distribution to the corresponding negative exponential distribution that would have occurred if the rat had emitted the same number of responses randomly in time, at the same rate. The comparison of the obtained distributions with corresponding negative exponentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
99
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(107 citation statements)
references
References 39 publications
8
99
0
Order By: Relevance
“…The most successful example of the former category are delaydiscounting paradigms in which impulsive choice is defined as the selection of a small but immediate reward over a larger but delayed one (Evenden and Ryan, 1996;Mazur, 1987;Richards et al, 1999;Wogar et al, 1993). In the latter category, it has also proved possible to assess the ability of an animal to withhold from making a response, for example in differential reinforcement of low-rate schedules (DRL) (eg Fletcher, 1995;Richards et al, 1993), and in 'go/no-go' tasks (eg Harrison et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The most successful example of the former category are delaydiscounting paradigms in which impulsive choice is defined as the selection of a small but immediate reward over a larger but delayed one (Evenden and Ryan, 1996;Mazur, 1987;Richards et al, 1999;Wogar et al, 1993). In the latter category, it has also proved possible to assess the ability of an animal to withhold from making a response, for example in differential reinforcement of low-rate schedules (DRL) (eg Fletcher, 1995;Richards et al, 1993), and in 'go/no-go' tasks (eg Harrison et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Responses emitted before the criterion time are not reinforced, but instead reset the experimental clock, forcing the subject to withhold responding again until the criterion time has passed. Hence, this schedule can access both the self-paced timing ability of subjects, as well as their capacity to inhibit impulsive responding following errors (e.g., Richards et al 1993;Evenden 1999;Ripley et al 2001). We utilized a series of DRL schedule values in order to study emotional behavior as indexed by premature burst responding, as well as memory endurance indexed by the resistance to change during the transition from one criterion time to another.…”
mentioning
confidence: 99%
“…It is possible that the effects of SSR149415 and SSR125543 on DRL-72 s performance result from an interaction with monoaminergic systems, such as the serotonergic (5-HT) and norepinephrine (NE) neurotransmissions (Carrasco and Van de Kar, 2003;Lowry et al, 2000;Day et al, 2004;Price et al, 1998). It has been demonstrated that the activity of classical antidepressants in DRL-72 s schedules relies on their ability to modulate 5-HT and NE neurotransmission (Britton and Koob, 1989;Richards and Seiden, 1991;Richards et al, 1993;Balcells-Olivero et al, 1998;Dekeyne et al, 2002). Experiments with the CRF1 receptor antagonist CP154,526 have shown that this compound did not alter basal levels of cortical 5-HT, NE, and dopamine, in freely moving rats (Millan et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The following parameters were automatically recorded by the Med-PC software: the total number of lever-presses emitted during the session, the number of food pellets obtained (ie the number of reinforced responses), and the inter-response time (IRT, the time elapsed between two lever-presses; Richards et al, 1993). IRTs were subsequently split into nine bins (IRT bin (0-12 s), IRT bin (13-24 s),y, IRT bin (85-96 s), and IRT bin (496 s)).…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation